P53 tumor suppressor and iron homeostasis. (4th September 2018) - Zhang, Jin; Chen, Xinbin
Abstract : Iron is an essential nutrient for all living organisms and plays a vital role in many fundamental biochemical processes, such as oxygen transport, energy metabolism, and DNA synthesis. Due to its capability to produce free radicals, iron has deleterious effects and thus, its level needs to be tightly controlled in the body. Deregulation of iron metabolism is known to cause diseases, including anemia by iron deficiency and hereditary hemochromatosis by iron overload. Interestingly, dysregulated iron metabolism occurs frequently in tumor cells and contributes to tumorigenesis. In this review, we will discuss the role of p53 tumor suppressor in iron homeostasis. Abstract : P53 tumor suppressor plays a critical role in maintaining the genome integrity. Recent studies show that p53 is instrumental in regulating iron homeostasis by modulating several iron regulators. Some iron regulators also form a feedback regulatory loop with p53. Thus, the crosstalk between p53 and the iron regulators may shed a light on the mechanisms by which iron metabolism is altered in cancers.